The Contribution of Artificial Intelligence Technology to the Learning Process of Accounting Students in the Digital Era and Learning Ethics - Lelahester Rina; Lamin Kaira; Gehad Mohammed Sultan Saif; Wulan Setyaningsih (Advances Educational Innovation, 2024)
Objective: This study investigates the contribution of Artificial Intelligence (AI) technology to the learning process of accounting students in Surakarta, focusing on its adoption and associated learning ethics in the digital era.Methods: A quantitative approach was employed using a questionnaire distributed via Google Forms, targeting accounting students from private and state universities. The analysis utilized SmartPLS 3 for Partial Least Squares Structural Equation Modeling (PLS-SEM).Findings: The results indicate that Perceived Ease of Use significantly influences AI Technology Adoption, while Technology Readiness positively impacts both Perceived Usefulness and Perceived Ease of Use. However, Technology Readiness shows no significant effect on AI Technology Adoption. This highlights the critical role of ease of use over perceived usefulness in driving technology adoption among students.Novelty: This research contributes to the existing literature by demonstrating the nuanced relationships between technology readiness, perceived ease of use, and the adoption of AI technologies in accounting education, specifically in a developing context.Theory and Policy Implications: The findings suggest that educational institutions should focus on enhancing students' technological readiness and simplifying AI interfaces to promote adoption. This has implications for curriculum design and policy formulation aimed at effectively integrating AI technologies into accounting education.